2019
DOI: 10.1371/journal.pone.0220493
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between suicidal ideation and family problems among young callers to the Japanese crisis hotline

Abstract: Previous studies have reported an association between family relationships and suicidal behavior, and found that people with high suicidal ideation are not likely to consult with others about their distress. An effective consulting service is therefore necessary for such individuals. Crisis hotlines are effective for reducing suicide risk, but their associated suicide ideation rate and odds ratio of family problems children remain unclear. The present study investigated the suicidal ideation rate and odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
3
5
0
1
Order By: Relevance
“…However, conscientiousness, which is usually associated with a lower level of depression [ 20 ], was associated with a higher risk of suicidal ideation in our population. Previous studies showed that a variety of family problems are associated with suicidal behaviors, and the present results are consistent with previous literature [ 21 , 22 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, conscientiousness, which is usually associated with a lower level of depression [ 20 ], was associated with a higher risk of suicidal ideation in our population. Previous studies showed that a variety of family problems are associated with suicidal behaviors, and the present results are consistent with previous literature [ 21 , 22 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This means when the division of labor and completion of family members worsen off, and domestic care and attention decrease, patients are more likely to develop SA. Such finding is consistent with the previous studies, which suggested that adolescents who communicate openly with their parents have better adaptability, that parental support and emotional support can effectively prevent SA, and that active family processes play a vital role in protecting adolescents (55). Family dysfunction is not only related to adolescent suicide but is also considered to be a risk factor for suicide in old age, because when family functioning fails, the quality of care and quality of life of the elderly cannot be guaranteed (56)(57)(58).…”
Section: Discussionsupporting
confidence: 93%
“…Obstruction created by the family members in romantic relationships confirms the fact that families may trigger suicidal behaviour (Murphy, 1999). In particular, complicated family relationships or physical abuse are strongly associated with suicidal behaviour (Ohtaki et al, 2019). For example, the distress imposed on men by their fathers (superior hegemony) complicates the situation, and physical abuse by their fathers is a source of humiliation and dishonour.…”
Section: Discussionmentioning
confidence: 99%